USE OF FINISHING AND DECORATING METHODS OF FINISHED CRUST PRODUCTS IN FOOTWEAR DESIGN - BABYCH АNTONINA; LYPSKI, TIMOFEY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The use of classic and innovative methods of decorating finished products from Krust of various designs when creating a unique design of single models or collections of shoes attracts the attention of fashion industry specialists from different countries of the world, starting with interesting and creative ideas in the form of sketches and ending with the final stage of work, their embodiment in the material. Creating a shoe design from Krust by decorating or decorating ready-made products of the same or different designs with surface coating, decorating the workpiece with application, tinting or painting is a bold challenge of the designer to society, his creative idea of ​​vision of the world of emotions, fashion and beauty. Since it is possible to decorate and decorate finished products in different ways, both new and used, this is partly an opportunity to save natural and industrial resources, if we are talking about natural Krust leather for the production of shoes, as well as an opportunity to reduce the amount of waste in this segment of products through their aesthetic renewal in this way. The article researched, analyzed and proved in a theoretical and practical way the question of the relevance and technological possibility of using the methods of finishing and decorating ready-made shoes from Krust in the design of single copies and collections of shoes. The issue of using the Critical Fashion Practice methodology in researching shoe design has been analyzed, and the theoretical feasibility of this development has been proven. A comparative analysis of education systems for the design of fashion industry products and the history of fashion is given. The results of theoretical and practical research on the possibility of using bold constructive and decorative ideas and technological solutions in different assortments of Krust shoes are given. Sketch design projects of single models and collections of shoes from Krust were developed, based on which samples and capsule collections of products decorated with various methods were made to visualize the authors’ idea. These developments were made in the conditions of the shoe hub of the Department of Fashion Technology of KNUTD and presented at international contests of young designers "Constellation Chestnuts" and "Cave Chestnuts", Kyiv KNUTD (2024).